Comparisons of open surgical repair, thoracic endovascular aortic repair, and optimal medical therapy for acute and subacute type B aortic dissection: a systematic review and meta-analysis - Jianping Liu; Xiaohong Chen; Juan Xia; Long Tang; Yongheng Zhang; Lin Cao; Yong Zheng (BMC Cardiovascular Disorders)
Abstract Background Various treatments have been employed in managing type B aortic dissection (TBAD), encompassing open surgical repair (OSR), thoracic endovascular aortic repair (TEVAR), and optimal medical therapy (OMT). Nonetheless, the determination of the most efficacious treatment protocol remains a subject of debate. We aim to compare the treatments in patients with acute and subacute TBAD using a meta-analytic approach. Methods A systematic search was conducted across databases including PubMed, EmBase, and the Cochrane Library for relevant studies published from their inception up to September 2024. Studies comparing OSR, TEVAR, and OMT for TBAD through controlled or direct comparative designs were incorporated. Pairwise comparison meta-analyses were performed employing odds ratios (OR) alongside 95% confidence intervals (CIs) to quantify intervention effects by using the random-effects model. Results Thirty-one studies involving 34,681 patients with TBAD were included in the final meta-analysis. We noted OSR were associated with an increased risk of in-hospital mortality (OR: 2.41; 95%CI: 1.67–3.49; P < 0.001), paraplegia (OR: 3.60; 95%CI: 2.20–5.89; P < 0.001), limb ischemia (OR: 7.80; 95%CI: 2.39–25.49; P = 0.001) and bleeding (OR: 9.54; 95%CI: 6.57–13.85; P < 0.001) as compared with OMT. Moreover, OSR versus TEVAR showed an increased risk of in-hospital mortality (OR: 2.67; 95%CI: 1.92–3.72; P < 0.001), acute renal failure (OR: 1.98; 95%CI: 1.61–2.42; P < 0.001), myocardial infaraction (OR: 2.76; 95%CI: 1.64–4.65; P < 0.001), respiratory failure (OR: 2.19; 95%CI: 1.73–2.76; P < 0.001), or bleeding (OR: 1.88; 95%CI: 1.33–2.67; P < 0.001), and lower risk of reintervention (OR: 0.30; 95%CI: 0.10–0.89; P = 0.030). Finally, TEVAR was associated with an increased risk of stroke (OR: 1.77; 95%CI: 1.41–2.21; P < 0.001), limb ischemia (OR: 13.00; 95%CI: 4.33–39.06; P < 0.001), and bleeding (OR: 3.65; 95%CI: 2.40–5.55; P < 0.001) as compared with OMT. Conclusions This study systematically compared various treatments and showed their safety and efficacy for acute and subacute TBAD. The results require further large-scale randomized controlled trials.